Реалізація алгоритму EKF SLAM на базі програмного пакету MATLA - Чекубашева, В. А. (ХНУРЕ, 2021)
The method of simultaneous localization and mapping (SLAM) of an unknown space considered in this article. Today, special attention is paid to the automation of complex, harmful, tedious and monotonous work in various fields. One of these is the study of unknown areas, where the penetration of people is impossible due to the mismatch of the microclimate, chemical/biological contamination or landslides etc. This implementation is based on the MATLAB program. The errors analysis graphs were obtained. They show errors that accumulate over time.
Keywords: Реалізація алгоритму EKF SLAM; акет MATLA